1997
DOI: 10.1089/hum.1997.8.15-1815
|View full text |Cite
|
Sign up to set email alerts
|

Selective Immunoaffinity-Based Enrichment of CD34+Cells Transduced with Retroviral Vectors Containing an Intracytoplasmatically Truncated Version of the Human Low-Affinity Nerve Growth Factor Receptor (ΔLNGFR) Gene

Abstract: Human hematopoietic stem cells remain one of the most promising target cells for gene therapeutic approaches to treat malignant and nonmalignant diseases. To rapidly characterize transduced cells and to isolate these from residual nontransduced, but biologically equivalent, cells, we have used a Moloney murine leukemia virus (Mo-MuLV)-based retroviral vector containing the intracytoplasmatically truncated human low-affinity nerve growth factor receptor (deltaLNGFR) cDNA as a marker gene. Supernatant transducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 35 publications
1
42
0
Order By: Relevance
“…Such a procedure is relatively well tolerated, avoids the use of mutagenic agents, and is compatible with clinically approved systems for cell processing. 15,30,31 Although the present study revealed an intact hematopoiesis after transplantation of immunoselected transgenic HSCs in secondary recipients, the clinical utility will be dependent on the demonstration of polyclonal reconstitution following selection prior to primary BMT. Since CD34 is expressed in clinically used HSC populations, human tCD34 cannot currently be proposed for clinical use, except when introduced into subpopulations that are CD34-negative (such as T cells).…”
Section: Discussionmentioning
confidence: 74%
“…Such a procedure is relatively well tolerated, avoids the use of mutagenic agents, and is compatible with clinically approved systems for cell processing. 15,30,31 Although the present study revealed an intact hematopoiesis after transplantation of immunoselected transgenic HSCs in secondary recipients, the clinical utility will be dependent on the demonstration of polyclonal reconstitution following selection prior to primary BMT. Since CD34 is expressed in clinically used HSC populations, human tCD34 cannot currently be proposed for clinical use, except when introduced into subpopulations that are CD34-negative (such as T cells).…”
Section: Discussionmentioning
confidence: 74%
“…Cells were infected at high densities (1 × 10 6 /ml) with retroviral vectors encoding as a gene transfer marker a truncated human low-affinity nerve growth factor receptor (⌬LNGFR) lacking the intracytoplasmatic domain. 6,12 The use of surface proteins as gene transfer markers allows rapid and convenient determination of gene transfer efficiencies by flow cytometry. 13 The vectors were produced by a PG13 producer cell line, 14 which utilises the Gibbon ape leukaemia virus (GALV) env protein.…”
mentioning
confidence: 99%
“…These were the cytoplasmic marker enhanced green fluorescent protein (EGFP, or simply ␥ in our vector nomenclature), 12 and the cell surface marker, low affinity nerve growth factor receptor lacking the cytoplasmic signal transduction domain (⌬LNGFR, or simply ␦). 13 Expression of these genes allows preparative sorting of transduced cells by flow cytometry (EGFP) 14 or, which may be of greater utility for clinical settings, also by immunoaffinity (⌬LNGFR). 13 However, potential drawbacks such as immunogenicity (EGFP) or interference with signalling pathways (⌬LNGFR) still remain to be elucidated.…”
Section: From Plasmid R250-mesv-dlngfr-sa-mneo Using Primers Kdelta+nmentioning
confidence: 99%
“…13 Expression of these genes allows preparative sorting of transduced cells by flow cytometry (EGFP) 14 or, which may be of greater utility for clinical settings, also by immunoaffinity (⌬LNGFR). 13 However, potential drawbacks such as immunogenicity (EGFP) or interference with signalling pathways (⌬LNGFR) still remain to be elucidated. 15 In the present study, we preferentially addressed the utility of these genes as reporters for vector expression.…”
Section: From Plasmid R250-mesv-dlngfr-sa-mneo Using Primers Kdelta+nmentioning
confidence: 99%